Doctor Dolittle - Claude , Jean (London Campbell Books, 2019)
Push, pull and turn mechanisms bring Doctor Dolittle and his menagerie of animals to life as he goes on an adventure to Africa. First Stories: Doctor Dolittle is the perfect introduction for young children to this popular tale
English stories
Keywords: Children's stories; Fiction